Twenty-five years of advocacy for patients with gastroparesis: support group therapy and patient reported outcome tool development. Issue 1 (December 2016) - Cutts, Teresa; Holmes, Sandra; Kedar, Archana; Beatty, Karen; Mohammad, Mohammad; Abell, Thomas
Abstract Background Gastroparesis (Gp) is a poorly understood chronic gastrointestinal medical condition for which patient reported outcomes (PRO) are lacking. Previously developed symptoms scoring has been used for several decades. Using symptoms scores as a basis for documentation, 12 years of support/focus group patient feedback from the nearly 1000 attendees were integrated with medical care and recommendations for treatment were developed. Early attenders of the support group were compared with non-attendees for illness acuity, disability, and duration and number of office phone calls. Methods Patients cared for in an academic medical practice were assessed for patient-derived PRO symptoms, coupled with standardized Health Related Quality of Life (HRQOL) measures. Based on factors identified by the patients via support/focus groups, a diagnostic and prognostic tool was developed. Results The new tool utilized PRO symptoms and included provider assessments of medical illnesses as well as resource utilization. This 'post PRO' tool has been applied in a variety of settings for patients with the symptoms of Gp over the last two decades. The 'pre-PRO' factors from the support/focus groups were compared to the PRO measures as well as the 'post-PRO' scale to assess their usefulness. Using methods that combine chart data, including electronic medical records (EMR), with PRO symptoms may have design implications for PRO assessment. The resultant scales, as part of a new tool, can allow for sharing of PRO derived scores in a chronic gastrointestinal (GI), illness with different practitioners. Conclusions These newly-derived scales offer a potentially useful tool for clinical decision-making, tailoring treatment to patient subgroups and engaging both patients and their families and caregivers in more active partnerships with providers to improve health outcomes.